Taxonomic Characterization and Antibacterial Activity of some Mosses of District Bagh Azad Jammu and Kashmir (Western Himalaya), Pakistan - Shamsa Nazir M Nazir Kayani (Kashmir Journal of Science, 2023)
District Bagh is a biodiversity rich area of Azad Jammu and Kashmir. However, the exploration of bryoflora has been neglected due to many reasons. The current research project is the first attempt to explore moss flora of the area. As part of the ongoing studies, five different sites were surveyed during March to June, 2020. Collected species were identified by comparing with different bryophytes floras. The taxonomic studies of the species was carried out by using stereomicroscope, compound microscope and photomicroscope. Antibacterial activity of three different solvent extracts (ethanol, methanol and water) was evaluated against Acromobacter xyloxoxidans (Gram-negative) and Bacillus licheniformis (Gram-positive) bacteria by using disc diffusion method. A total of eight species were collected between 1510-1980m altitudes. The results of antibacterial activity showed that different moss extract retained different impact on the growth of bacteria. It has been find out that ethanol extract exhibited highest potency as compared to other solvents against both bacterial strains. In general, Gram- negative bacteria showed more resistance as compared to Gram- positive bacteria. The aqueous extract of most of the species was inactive against both tested bacterial strains. All extracts of Phelonotis fontana, Tortula sabulata and Grimmia montana showed positive results against both bacterial, whereas maximum susceptibility was demonstrated by Erythrodontum julaceum. Present study will open fresh avenue to use these identified moss species for the biochemical characterization.